Economic potential and environmental impacts of reused steel structures. Issue 4 (2nd April 2020) - Vares, Sirje; Hradil, Petr; Sansom, Michael; Ungureanu, Viorel
Abstract: Considerable amounts of natural resources are embodied in the building stock and infrastructure. Designing resource-efficient buildings is, therefore, an important approach to reduce raw material use and environmental impacts. However, sustainability criteria in national building codes focus primarily on improving energy efficiency and waste recovery. The EU target to recover 70% of construction and demolition waste is already being achieved in many countries; however, this is achieved using the lowest levels of the waste management hierarchy. Although landfill is avoided, the retained value of recovered products is generally low and there is a need to prioritise higher levels of recovery, i.e. reuse and waste prevention. Targets for this higher level of utilisation are currently unavailable, although they can be expected to be included in future European waste legislation. Consequently, the reuse of building structures is still uncommon and is not largely supported through regulation. The building stock is not designed for deconstruction, and material recovery for reuse at the end of life of buildings is complex and challenging. To support greater reuse of steel structures, this paper demonstrates the calculation of the economic potential and environmental impact of reused steel building elements.